2009
DOI: 10.1590/s1807-59322009000800004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Late Treatment on How Chronic Myeloid Leukemia Responds to Imatinib

Abstract: INTRODUCTIONIn Brazil, patients with chronic myeloid leukemia (CML) in the chronic phase were not given first-line imatinib treatment until 2008. Therefore, there was a long period of time between diagnosis and the initiation of imatinib therapy for many patients. This study aims to compare the major molecular remission (MMR) rates of early versus late imatinib therapy in chronic phase CML patients.METHODSBetween May 2002 and November 2007, 44 patients with chronic phase CML were treated with second-line imati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…However, increasing numbers and the molecular complexity of these subclones are correlated with rate and depth of response to TKI therapy which is, in turn, associated with the probability of achieving and maintaining a DMR. This vision is also supported by the observations that a delay in starting the TKI therapy after diagnosis, allowing for a longer interval that can favour the natural tendency of the Ph+ clone to evolve and to generate resistant subclones, is associated with a lower probability of response (Scerni et al , ); a higher degree of subclonal complexity has been found to correlate with the risk of the disease (Branford et al , ).…”
Section: Relevance Of the Depth And Duration Of The Molecular Responsementioning
confidence: 90%
“…However, increasing numbers and the molecular complexity of these subclones are correlated with rate and depth of response to TKI therapy which is, in turn, associated with the probability of achieving and maintaining a DMR. This vision is also supported by the observations that a delay in starting the TKI therapy after diagnosis, allowing for a longer interval that can favour the natural tendency of the Ph+ clone to evolve and to generate resistant subclones, is associated with a lower probability of response (Scerni et al , ); a higher degree of subclonal complexity has been found to correlate with the risk of the disease (Branford et al , ).…”
Section: Relevance Of the Depth And Duration Of The Molecular Responsementioning
confidence: 90%
“… 18 Scerni et al found that the probability of achieving MMR was significantly higher (60%) in Brazilian patients who received IM within one year of diagnosis than in those who started treatment more than one year after diagnosis (40%). 19 …”
Section: Discussionmentioning
confidence: 99%
“… 13 This delay is particularly experienced by patients waiting to access the limited number of specialized hematology centers. The optimal management of AML and other hematological malignancies 14 necessitates a prompt diagnosis and the initiation of treatment without delay.…”
Section: Discussionmentioning
confidence: 99%